Peirce Semiotic Analysis of the Representation Of Oligarchic Power in the Korean Drama Film the Healer - Septiana, Rizka (JURNAL KOMUNIKASI INDONESIA, 2023)
This study uses an interpretive/constructive paradigm and a qualitative approach using semiotic methods in its discussion. The purpose of this study is to show how a Korean drama film becomes a medium of representation or picture of reality, especially regarding the oligarchic power in the democratic history of South Korea at that time. This study will focus more on signs that describe or show the activities of oligarchic power in the Korean drama film The Healer. By using triadic analysis of Charles Oligarchy's semiotics, namely objects, interpretants and representatives, the researchers found that the semiotics of oligarchic power in the Korean drama film The Healer is illustrated by the use of the word "we" in the dialogue and enters the type of oligarchic power of collective rulers. The researcher concludes that the scenes and dialogues that show the activities of the power holder in the form of scenes and dialogues are representations. The object in the Korean drama film The Healer is shown through the activities of the oligarchic power, which is shown by expressions, dialogues and visible actions. Meanwhile, the interpretation of the meaning of oligarchic power appears in mind related to the object being referred to.